Mechanism of Methane Adsorption/Desorption in Low-Rank Vitrain and Durain Coal Affected by Pore Structure and Wettability: A Case Study in Dafosi Area, South Ordos Basin, China - Tao Peng; Yue Chen; Liya Wang; Dongmin Ma; Guofu Li; Weibo Li; Chao Zheng; Yusong Ji; Zhuoyuan Ma; Peng Hui; Xin Wang (Energies, 2022)
Water content and water–coal interface wettability are always the difficult issues of coalbed methane adsorption/desorption. In order to study the effects of the pore structure and wettability of different macro coal components on methane adsorption and desorption, we compared and analyzed the wettability difference between vitrain and durain, and revealed the influence of wettability on methane adsorption and desorption through a pore structure analysis, wettability measurements, an adsorption–desorption experiment and adsorption heat calculations under different conditions, taking the No. 4 coal in Dafosi Coal Mine of the Huanglong coalfield as the research object. The results show that both vitrain and durain are relatively hydrophilic substances. However, vitrain has a low ash content, high volatility, and less oxygen, and the pores are mainly semi-closed pores compared with dark coal. Vitrain also has poor connectivity, poor sorting, a small pore diameter, and a coarser surface, resulting in poor surface wettability. The large specific surface area (SSA) and relatively poor wettability of vitrain leads to more adsorption sites in methane, which makes the adsorption capacity of vitrain greater than that of durain, but the good pore connectivity of durain causes the strong desorption capacity of durain. The isosteric adsorption heat of the adsorption process is greater than that of the desorption process, indicating that there is a desorption hysteresis phenomenon which is essentially due to the lack of energy in desorption. Surfactants change the wettability of the coal surface, and different surfactants have different effects on methane adsorption and desorption. Relatively speaking, the methane desorption of coal samples treated with G502 and 6501 are better. The research results provide scientific reference for the study of gas–water transport in the desorption process of low-rank CBM, and provide evidence for the methane desorption model of vitrain and durain.